Method for the placement of palatal implants - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2002)
Purpose: Palatal implants have been used in the last 2 decades to eliminate headgear wear and to establish stationary anchorage. The aim of this investigation was to establish a method and easy protocol for palatal implant placement. Materials and Methods: The study comprised 8 male and 15 female patients each having a 4.5 x 8-mm stepped screw titanium implant placed in the palatal region for orthodontic purposes. A surgical template containing metal drill housing was prepared. Angulation of the drill housing was controlled according to the radiologic tracing of the maxilla transferred to a plaster cast section in the paramedian plane. Implants were placed using a noninvasive technique (incision, flap, and suture elimination) and left transmucosally to facilitate the surgical procedure and reduce operations. The paramedian region was selected so as to avoid connective tissues of the palatine suture and because it was considered to be a suitable host site for implant placement. Results: After 3 months of heating, all implants were osseointegrated and no implant was lost throughout the orthodontic treatment. Discussion: Palatal implants can be used effectively for anchorage maintenance and space-gaining procedures, Conclusion: Usage of a 3-dimensional surgical template eliminated faulty implant placement, reduced chair time, and minimized trauma to the tissues while enhancing osseointegration.
Keywords: anchorage; Class II malocclusion; dental implants; molar distalization; molar slider; noncompliance therapy; orthodontics; palatal implant; RIGID ENDOSSEOUS IMPLANTS; OSSEOINTEGRATED IMPLANTS; ORTHODONTIC ANCHORAGE; TITANIUM IMPLANTS; MOLARS